Influence of Pomelo Albedo on Characteristics of Chicken Sausage Emulsion Systems - Srithongkerd, Monruthai; Watcharakhun, Jirawan; Morntanom, Kawin (Journal of Food Health and Bioenvironmental Science, 2018)
The purpose of this research was to study the effect of the addition of albedo from pomelo peel on the properties of meat emulsions. The meat emulsion models were prepared by increasing the concentration of the albedo from pomelo peel (fresh and dried) from 0, 2.5, 5, 7.5 and 10% (by weight). The analysis of the forming stability, color, viscosity and flow of emulsion was carried out. It was found that the addition of albedo from the pomelo peel resulted in increased the stability and occurrence of emulsion; the maximum values were reached with the inclusion of 5 percent albedo. The stability of the emulsion was higher with albedo inclusion under non-dried conditions and also resulted in lower brightness values for a* and b* and increased viscosity. Emulsions that included dry albedo were not as viscous as emulsions that included fresh albedo. Ultimately, this study demonstrates that albedo, Addition of pomelo albedo at 5% can be improved and developed the chicken sausage. Moreover, the addition of fresh pomelo albedo resulted in chicken sausage has good characteristic which affected on consumer’s acceptance of all attribute. For sensory evaluation, acceptance score from consumer in appearance, color, flavor, hardness, elasticity and overall liking were 8.56±0.64, 8.36±0.75, 8.40±0.61, 8.24±0.59, 8.18±0.52, 8.20±0.53 and 8.16±0.58, respectively at a level of p value < 0.05.